Tantangan Dan Peluang Dalam Pengembangan Laporan Keuangan Syariah: Studi Literatur - Warahma, Izrha; Subhan, Muhammad (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2025)
Sharia financial reports have an important role in the development of the sharia financial industry. However, its development is still faced with various challenges. This research aims to identify challenges and opportunities in developing sharia financial reports through literature studies. The research method used is literature study by analyzing various journals, books and related documents. The research results show that the main challenges include a lack of global standardization, limited human resources, differences in interpretation of sharia principles, and information technology constraints. On the other hand, some opportunities can be exploited, such as increasing market demand, government support, research development, and international cooperation. It is hoped that this research can contribute to the development of sharia accounting theory and provide input for policy makers, accounting practitioners and academics.